New tapered metallic stent for unresectable malignant hilar bile duct obstruction - Sakai, Yuji (World J Clin Cases, 2015)
AIM: To examine the usefulness of a new tapered metallic stent (MS) in patients with unresectable malignant hilar bile duct obstruction. METHODS: This new tapered MS was placed in 11 patients with Bismuth II or severer unresectable malignant hilar bile duct obstruction, as a prospective study. The subjects were six patients with bile duct carcinoma, three with gallbladder cancer, and two with metastatic bile duct obstruction. Stenosis morphology was Bismuth II: 7, IIIa: 3, and IV: 1. UMIN Clinical Trial Registry (UMIN000004758). RESULTS: MS placement was 100% (11/11) successful. There were no procedural accidents. The mean patency period was 208.401 d, the median survival period was 142.000 d, and the mean survival period was 193.273 d. Occlusion rate was 36.4% (4/11); the causes of occlusion were ingrowth and overgrowth in 2 patients each, 18.2%, respectively. Patients with occlusion underwent endoscopic treatment one more time and all were treatable. CONCLUSION: The tapered MS proved useful in patients with unresectable malignant hilar bile duct obstruction because it provided a long patency period, enabled re-treatment by re-intervention, and no procedural accidents occurred.